Enhancing ceramic product value through appropriate production techniques - Olalere, Folasayo Enoch; Ab. Aziz Shuaib; Abu Hassan Hasbullah (2014)
Launching new products is an essential attributes of successful businesses as they survive and grow; and the ability to develop these new products to compete in existing or new markets is a core competency of many successful firms. The process of developing new products begins with a well conceived design, developed into prototype. In ceramics production, the manual process of developing product idea by hand turning or hand carving design concept in plaster is slow, inaccurate and demands skilled persons that are difficult to find and too much time consuming to train; thereby, tends to decrease product competitiveness. Thus, engaging technology, by developing and conducting test digitally, and generating rapid prototype from CAD model is seen as a viable approach that can help improve product quality and get product faster to market. Therefore, this paper seeks to investigate the viability of rapid prototyping technology in enhancing product value. The paper also illustrates on how designers can integrate aesthetic appeals in product by analyzing designs using PhiMATRIXTM Software.